Places of memory in modern China (Leiden ; Boston)
x, 285 sayfa
Keywords: “In the last decades, the scholarship on issues of national and cultural identity of China has been constantly on the rise. This edited volume aims at addressing these issues by applying Pierre Nora’s approach of places of memory ( lieux de mémoire ) to the Chinese context. The volume assembles a number of articles that focus on the most significant places of memory in modern and contemporary China, ranging from Qin Shihuang’s Terracotta Warriors to the Chiang Kai-shek Memorial Hall. The genesis and nature of these places are discussed in detail by combining approaches of both cultural and historical sciences. In addition, issues of cultural memory and politics are addressed in order to question the ideological construction of these places.” --